Yokukansankachimpihange Is Useful to Treat Behavioral/Psychological Symptoms of Dementia - Katsumoto, Eiichi; Ishida, Toru; Kinoshita, Kenji; Shimizu, Miho; Tsutsumi, Toshihito; Nagai, Yoko; Nishimura, Masakazu; Yokouchi, Toshio; Yoshida, Yasushi (Frontiers in Nutrition, 2021)
Yokukansankachimpihange is a Chinese herbal medicine reported to benefit anxiety and sleep disorders, and it recently has been introduced to treat behavioral and psychological symptoms of dementia. There are no multicenter studies of its effectiveness regarding dementia in Japan, and this study’s main objective was to clarify the effects of Yokukansankachimpihange on behavioral and psychological symptoms of dementia in a sample of patients from multiple healthcare centers. Nine facilities affiliated with Osaka Association of Psychiatric Clinics participated in November 2013 through April 2015 and provided 32 Alzheimer’s disease patients to whom Yokukansankachimpihange was orally administered for eight weeks. During the study, the patients continued their regular medication regimens. Behavioral and psychological symptoms of dementia (Behavioral Pathology in Alzheimer’s Disease Rating Scale (Behave-AD)), core symptoms (Mini-Mental State Examination (MMSE)), activities of daily living (Nishimura Activity of Daily Living Scale (N-ADL)), and gastrointestinal symptoms (nausea/vomiting, loss of appetite, gastric discomfort, constipation, and diarrhea) were measured at baseline, after four weeks of treatment, and after eight weeks of treatment. Yokukansankachimpihange was orally administered at a dosage of 7.5 g twice daily before or between meals for eight weeks. The Behave-AD mean score significantly improved after eight weeks of treatment. There were no significant changes in MMSE, N-ADL, or gastrointestinal symptoms; however, decreased gastrointestinal scores were observed after eight weeks. There were no side effects related to Yokukansankachinpihange. Pharmaceutical treatments are important for treating behavioral and psychological symptoms of dementia, and this study confirmed Yokukansankachimpihange’s efficacy for treating Alzheimer’s disease. Because the aggressiveness and sleep disorder components of the Behave-AD construct were the most improved symptoms, and those symptoms are known to significantly burden dementia patients’ caregivers, Yokukansankachimpihange’s efficacy might indirectly relieve these caregivers’ burden of care.